Synthesis, magnetic properties and enhanced photoluminescence of Fe3O4-ZnO heterostructure multifunctional nanoparticles - Chu, Tien Dung (H. : ĐHQGHN, 2017)
In this paper, Fe3O4-ZnO heterostructure multifunctional nanoparticles (NPs) were successfully prepared in aqueous solution by ultrasound assisted thermolysis. First, iron oxide (Fe3O4) magnetic NPs were prepared by co-precipitation method. The Fe3O4 NPs were modified by 3-aminopropyltriethoxysilane (APTES) to have free amine (-NH2) groups on their surface, then, Zn2+ ions were added and stirred to adsorb onto the surface of Fe3O4-NH2 NPs in alkaline solution at a pH of 11. This solution was decomposed through thermolysis in ultrasound bath. The results of measurements show that photoluminescence of Fe3O4-ZnO heterostructure multifunctional NPs was enhanced in visible light at 565 nm wavelength to allow detection, labeling, diagnosis, and therapy in biomedicine. Moreover, they exhibit superparamagnetic properties of Fe3O4 with high saturation magnetization (MS), which can be used for seperation application in biomedicine under an external magnetic field.